BRAF and MEK inhibitors affect dendritic cell maturation and T cell stimulation - Hoyer, Stefanie; Eberlein, V.; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie; Schaft, Niels; Dörrie, Jan (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

BRAF and MEK Inhibitors Affect Dendritic-Cell Maturation and T-Cell Stimulation - Hoyer, Stefanie; Eberlein, Valentina; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie; Schaft, Niels; Dörrie, Jan (International Journal of Molecular Sciences, 2021)
BRAF and MEK inhibitor (BRAFi/MEKi) combinations are currently the standard treatment for patients with BRAFV600 mutant metastatic melanoma. Since the RAS/RAF/MEK/ERK-pathway is crucial for the function of different immune cells, we postulated an effect on their function and thus interference with anti-tumor immunity. Therefore, we examined the influence of BRAFi/MEKi, either as single agent or in combination, on the maturation of monocyte-derived dendritic cells (moDCs) and their interaction with T cells. DCs matured in the presence of vemurafenib or vemurafenib/cobimetinib altered their cytokine secretion and surface marker expression profile. Upon the antigen-specific stimulation of CD8+ and CD4+ T cells with these DCs or with T2.A1 cells in the presence of BRAFi/MEKi, we detected a lower expression of activation markers on and a lower cytokine secretion by these T cells. However, treatment with any of the inhibitors alone or in combination did not change the avidity of CD8+ T cells in peptide titration assays with T2.A1 cells. T-helper cell/DC interaction is a bi-directional process that normally results in DC activation. Vemurafenib and vemurafenib/cobimetinib completely abolished the helper T-cell-mediated upregulation of CD70, CD80, and CD86 but not CD25 on the DCs. The combination of dabrafenib/trametinib affected DC maturation and activation as well as T-cell activation less than combined vemurafenib/cobimetinib did. Hence, for a potential combination with immunotherapy, our data indicate the superiority of dabrafenib/trametinib treatment.
Keywords: vemurafenib; dabrafenib; cobimetinib; trametinib; BRAF inhibitor; MEK inhibitor; DCs; T cells; immunotherapy; melanoma

Electroporated Antigen-Encoding mRNA Is Not a Danger Signal to Human Mature Monocyte-Derived Dendritic Cells - Hoyer, Stefanie; Gerer, Kerstin F.; Pfeiffer, Isabell A.; Prommersberger, Sabrina; Hoefflin, Sandra; Jaitly, Tanushree; Beltrame, Luca; Cavalieri, Duccio; Schuler, Gerold; Vera, Julio; Schaft, Niels; Dörrie, Jan (Journal of immunology research, 2015)
For therapeutic cancer vaccination, the adoptive transfer of mRNA-electroporated dendritic cells (DCs) is frequently performed, usually with monocyte-derived, cytokine-matured DCs (moDCs). However, DCs are rich in danger-sensing receptors which could recognize the exogenously delivered mRNA and induce DC activation, hence influencing the DCs' immunogenicity. Therefore, we examined whether electroporation of mRNA with a proper cap and a poly-A tail of at least 64 adenosines had any influence on cocktail-matured moDCs. We used 16 different RNAs, encoding tumor antigens (MelanA, NRAS, BRAF, GNAQ, GNA11, and WT1), and variants thereof. None of those RNAs induced changes in the expression of CD25, CD40, CD83, CD86, and CD70 or the secretion of the cytokines IL-8, IL-6, and TNFα of more than 1.5-fold compared to the control condition, while an mRNA encoding an NF-B-activation protein as positive control induced massive secretion of the cytokines. To determine whether mRNA electroporation had any effect on the whole transcriptome of the DCs, we performed microarray analyses of DCs of 6 different donors. None of 60,000 probes was significantly different between mock-electroporated DCs and MelanA-transfected DCs. Hence, we conclude that no transcriptional programs were induced within cocktail-matured DCs by electroporation of single tumor-antigen-encoding mRNAs.
CRIS-Team Scopus Importer:2021-10-01

Electroporation of mRNA as a Universal Technology Platform to Transfect a Variety of Primary Cells with Antigens and Functional Proteins - Sauerer, Tatjana; Albrecht, Leoni; Sievers, Nico M.; Gerer, Kerstin F.; Hoyer, Stefanie; Dörrie, Jan; Schaft, Niels (RNA Vaccines, 2024)
Electroporation (EP) of mRNA into human cells is a broadly applicable method to transiently express proteins of choice in a variety of different cell types. We have spent more than two decades to optimize and adapt this method, first for antigen-loading of dendritic cells (DCs) and subsequently for T cells, B cells, bulk PBMCs, and several cell lines. In this regard, antigens were introduced, processed, and presented in context of MHC class I and II. Next to that, functional proteins like adhesion receptors, T-cell receptors (TCRs), chimeric antigen receptors (CARs), constitutively active signal transducers (i.e. caIKK), and others were successfully expressed. We have also established this protocol under full GMP compliance as part of a manufacturing license to produce mRNA-electroporated DCs and mRNA-electroporated T cells for therapeutic applications in clinical trials. Therefore, we here want to share our universal mRNA electroporation protocol and the experience we have gathered with this method. The advantages of the transfection method presented here are: (1) easy adaptation to different cell types; (2) scalability from 106 to approximately 108 cells per shot; (3) high transfection efficiency (80–99%); (4) homogenous protein expression; (5) GMP compliance if the EP is performed in a class A clean room; and (6) no transgene integration into the genome. The provided protocol involves: OptiMEM® as EP medium, a square-wave pulse with 500 V, and 4 mm cuvettes. To adapt the protocol to differently sized cells, simply the pulse time has to be altered. Thus, we share an overview of proven electroporation settings (including recovery media), which we have established for various cell types. Next to the basic protocol, we also provide an extensive list of hints and tricks, which, in our opinion, are of great value for everyone who intends to use this transfection technique.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Antigen expression; B cell; CAR; GMP; Immunotherapy; Monocyte; Monocyte-derived DC (moDC); mRNA electroporation; NK cell; PBMC; Protein expression; T cell; TCR

Kosteneffekte durch nicht indizierte Diagnostik der Schilddrüse - Hafner, Lucas; Tomandl, Johanna; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Hoyer, Stefanie; Hueber, Susann; Donnachie, Ewan; Kühlein, Thomas (Deutsche Gesellschaft für Gesundheitsökonomie 11. Jahrestagung Gesundheitsverhalten und Prävention, 2019)
Einleitung Die Inzidenz von Schilddrüsenkarzinomen ist bei konstanter Mortalität in jüngerer Vergangenheit in Deutschland stark angestiegen. Dies ist vermutlich auf verbesserte Diagnosemöglichkeiten, die zur Entdeckung zahlreicher kleiner Schilddrüsenknoten führt, die unerkannt nie als medizinisches Problem in Erscheinung getreten wären. Wir untersuchen, ob nicht indizierte Diagnostik im Schilddrüsenkontext zu invasiven Behandlungen und infolge dessen hohen Kosten führt. Konkret untersuchen wir, ob sich durch eine nicht indizierte Sonographie der Schilddrüse die ambulanten, stationären sowie pharmazeutischen Gesundheitskosten bei den betroffenen Patienten kurz und langfristig erhöhen. Methoden Auf Basis von Routinedaten aus Deutschland werden Gesundheitskostenverläufe von Patienten untersucht, deren Symptomatik zu Beginn der Studie auf eine Fehlfunktion der Schilddrüse hindeuten. Bei allen betrachteten Patienten wurde zunächst per Blutuntersuchung der TSH-Wert bestimmt, mit dessen Hilfe Anomalien der Schilddrüsenfunktion identifiziert werden können. Als Interventionsgruppe werden die Patienten betrachtet, bei denen nicht leitliniengerecht, d.h. mit nur kurzem zeitlichen Abstand, zusätzlich eine Sonographie der Schilddrüse durchgeführt wird. Als Kontrollgruppe gelten Patienten ohne oder mit leitlinienkonformer Sonographie. Um mögliche Kosteneffekte der nicht leitliniengerechten Sonographie messen zu können, wird mittels eines Matching-Verfahren sichergestellt, dass sich beide Gruppen hinsichtlich Alter, Geschlecht, Wohnort, ambulantem Behandlungsanlass sowie Morbidität nicht unterscheiden. Ergebnisse Die durchschnittlichen Kosten für schilddrüsenspezifische ambulante Leistungen sowie schilddrüsenspezifische Arzneimittel sind in der Interventionsgruppe signifikant höher als in der Kontrollgruppe. Dieser Unterschied ist auch noch mehrere Jahre nach der Intervention zu beobachten. Allerdings ist der Anteil der schilddrüsenspezifischen Kosten an den Gesamtkosten in beiden Gruppen sehr gering. Hinsichtlich der durchschnittlichen Gesamtkosten (ambulant, stationär und pharmazeutisch) zeigen sich im Analysezeitraum keine signifikant unterschiedlichen Verläufe bei Interventions- und Kontrollgruppe. Fazit Unsere Ergebnisse liefern keine Evidenz dafür, dass eine nicht indizierte Sonographie der Schilddrüse Behandlungskaskaden auslöst, welche zu hohen allgemeinen Gesundheitskosten führt. Lediglich schilddrüsenspezifische Kosten sind nach der nicht indizierten Diagnostik selbst langfristig höher. Im Hinblick auf die Gesamtkosten fällt dieser Kostenunterschied allerdings nicht ins Gewich
Keywords: Gesundheitsökonomische Evaluation; Medizinische Überversorgung; Schilddrüsenerkrankungen

„Mind the gap“ – Verzahnung von Wissenschaft und hausärztlicher Praxis - Linking up Science and Family Practice - van der Keylen, Piet; Maun, Andy; Hoyer, Stefanie; Roos, Marco; Beier, Markus; Voigt-Radloff, Sebastian; Frank, Luca (Zeitschrift für Allgemeinmedizin, 2019)
Linking up science and daily practiceis a hallmark or research in family medicine. There is, however, an alarming gap between science and family practice. Due to their decentralized structures, family practices in particular are at risk of being excluded from the scientific developmental process. Within the prospective, multicenter, cluster-randomized GAP study (well-informed physician-patient communication in back pain), the use of an evidence-based internet portal for back pain consultations in family practice is being investigated. In this consortium project – financed by the innovation fund – an intervention through participatory and iterative procedures (integration of family practices) is developed. The new intervention presents medical evidence as communicable and consultable as possible. This article addresses the challenges of linking up science and family practice from the GAP study’s perspective. Family medicine plays an important role in the network of science and daily practice. On the one side, family practice itself is the object of investigation. On the other side, family practice also generates new research questions from everyday routine. The academic family physician – in a dual function as a scientist and family doctor – seems to be predestined to mind the gap between science and primary medical care.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Forschungsprojekte; Hausarztpraxen; hausärztliche Forschung; Praxisrekrutierung; Rückenschmerz

Preclinical evaluation of a combination of checkpoint blockade and dendritic cell vaccination against Merkel cell carcinoma - Sauerer, Tatjana; Gerer, K.; Hoyer, Stefanie; Erdmann, M.; Berking, Carola; Voll, R.; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Targeted label-free quantification of interleukin-8 in PMA-activated U937 cell secretome by nanoLC-ESI-MS/MS-sSRM. - Emirbayer, Pelin Esma; Gerer, Kerstin; Hoyer, Stefanie; Pischetsrieder, Monika (Proteomics, 2017)
Monocytes are a part of the innate immune system. Their differentiation into macrophages changes their cellular proteome and secretome. Particularly secretome components such as cytokines are crucial for immune response and inflammation in many diseases. Differentiation of human lymphoma cell line U937 can be triggered by phorbol 12-myristate 13-acetate (PMA). Screening of the cytokine release in U937 upon PMA stimulation by cytometric bead array almost exclusively showed interleukin-8. Next, a label-free nanoLC-ESI-MS/MS-sSRM method for quantification of interleukin-8 in the cell secretome was established and applied to monitor the time kinetics of PMA treatment in different concentrations. Targeted secretome analysis was achieved by scheduled SRM-MS using one proteotypic peptide as precursor ion and four mass transitions. Label-free quantification was performed by external calibration using interleukin-8 standard. Validation results indicated that the method was suited for the quantification of interleukin-8 in the secretome. The maximal interleukin-8 release of 62.4 ng/mL was observed after incubating cells treated by 50 ng/mL PMA for 48 h. The method can now be used for quantification of interleukin-8 release from different cells under various conditions. Furthermore, it can be easily expanded to other secreted proteins detected by untargeted screening methods. This article is protected by copyright. All rights reserve